2021
DOI: 10.1021/acs.langmuir.1c02321
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Capture and Low-Temperature Release by Poly(aminoethyl methacrylate) and Derivatives

Abstract: Poly­(aminoethyl methacrylate) (PAEMA), poly­(ethylene oxide)-block-(aminoethyl methacrylate) (PEO–PAEMA), and their guanidinylated derivates, poly­(guanidine ethyl methacrylate) (PGEMA) and poly­(ethylene oxide)-block-(guanidine ethyl methacrylate) (PEO–PGEMA), were prepared to study their capabilities for CO2 adsorption and release. The polymers of different forms or degree of guanidinylation were thoroughly characterized, and their interaction with CO2 was studied by NMR and calorimetry. The extent and kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In their recent study of guanidinylated poly-(methacrylates), Tiainen and colleagues observed a significant loss of capacity upon a single repeat cycle, ascribing this to incomplete thermally induced release of CO 2 . 38 Chemical decomposition of the guanidine group was not considered; we find PIM-guanidine to remain stable through 15 humid adsorption−desorption cycles conducted at desorption temperatures of 70−90 °C, and the material therefore appears to be recyclable under NGCC conditions.…”
Section: ■ Conclusionmentioning
confidence: 94%
See 1 more Smart Citation
“…In their recent study of guanidinylated poly-(methacrylates), Tiainen and colleagues observed a significant loss of capacity upon a single repeat cycle, ascribing this to incomplete thermally induced release of CO 2 . 38 Chemical decomposition of the guanidine group was not considered; we find PIM-guanidine to remain stable through 15 humid adsorption−desorption cycles conducted at desorption temperatures of 70−90 °C, and the material therefore appears to be recyclable under NGCC conditions.…”
Section: ■ Conclusionmentioning
confidence: 94%
“…Guanidine has previously been studied for CO 2 capture as both a sole sorbent and in combination with other Lewis bases, as it is a far better proton acceptor (Bro̷nsted base) than simple amines. This basicity allows guanidine to reversibly bind CO 2 from air to form a crystalline carbonate-carbamate salt, stabilized by guanidinium hydrogen bonding in the presence of water. Several groups have reported the use of oligomers or polymers with guanidine side chains , as well as guanidinylated polyamines impregnated in porous silicas, , for CO 2 capture. Here, we add the use of spirocyclic monomers and humidity in the sorption conditions by exploring the installation of guanidine groups on the PIM-1 polymer and the characterization of the resulting material as a polymeric CO 2 adsorbent.…”
Section: Introductionmentioning
confidence: 99%
“…Tiainen and co‐workers reported the preparation of poly(aminoethyl methacrylate) (PAEMA), poly‐(ethylene oxide)‐ block ‐(aminoethyl methacrylate) (PEO‐ b ‐PAEMA), and their guanidinylated derivates, namely PGEMA and PEO‐PGEMA, via RAFT polymerization to study their CO 2 adsorption properties. [ 209 ] It was found that these polymers exhibit high CO 2 capacity, with the highest value of 2.4 mmol g −1 at room temperature, achieved by PGEMA with 7% guanidinylation degree. Low desorption temperature was also observed, thus requiring low energy for regeneration.…”
Section: Alternative Synthesis Pathways Of Polymeric Materials For Co...mentioning
confidence: 99%
“…DAC operates at ambient conditions and avoids impurities that are common for point source capture of CO 2 , but the low concentration of CO 2 requires the movement of large volumes of air and strong adsorption of CO 2 . Many current DAC absorbents, such as liquid amines and solid alkali hydroxides, strongly bind CO 2 through chemisorption, requiring energy-intensive regeneration of the sorbent. , Metal–organic frameworks (MOFs) are a promising class of alternative sorbent materials for DAC allowing regeneration at relatively low temperatures. In contrast to sorbents such as alkali hydroxides, MOFs are modular, flexible, and highly tunable, and they possess remarkably high porosities, low densities, and long-range order .…”
Section: Introductionmentioning
confidence: 99%